Digital Phonics Literacy Media to Support the Initial Reading Skills of First-Grade Students in Multicultural Bilingual Schools - Adnyana, I Made; Arnyana, Ida Bagus Putu; Margunayasa, I Gede (Jurnal Pendidikan Multikultural Indonesia, 2023)
Literacy in Indonesia still needs to be improved, and the scope of literacy of students in Indonesia still needs to be narrower, including reading activities not understanding. This research aims to create Indonesian digital phonics literacy media for the beginning reading ability of first-grade students in multicultural elementary schools. The research was developed with the ADDIE model. The research subjects were experts, grade I elementary school teachers, and bilingual learners in multicultural schools. Data collection methods were observation, interview, test, and questionnaire. Data analysis was done with qualitative and quantitative descriptions. The analysis shows that Indonesian digital phonics literacy media consists of digital storybooks, posters, and phonic songs packaged in websites with Google site applications. Media, material, and language validity in Indonesian digital phonics literacy media is very high. Digital phonics literacy media shows a very practical category with a practicality level of 80%-100%, a teacher response score of 89.38%, and a response to the collaboration of parents and students of 88.75%. The effectiveness of the media shows a large category with a significant contribution to students' beginning reading skills. The effect size coefficient of the test shown is 1.53 and 1.86 on the results of the observation analysis of the beginning reading ability of bilingual learners in multicultural schools.